Análise comparativa entre vários métodos de quantificação de hemiceluloses da madeira de eucalipto Comparative analysis between several methods of quantification of eucalyptus wood hemicelluloses - Lívia P. S. Palmeiras; Andréia S. Magaton; Jorge L. Colodette; Ana Márcia Macedo Ladeira Carvalho (Química Nova, 2010)
Pulp hemicelluloses can be extracted with NaOH and quantified by colorimetric and gravimetric techniques. However the most usual methods to measure eucalyptus pulp hemicelluloses have been through the pentosan method or through xylan analyses by GC or HPLC techniques. In this study a comparison was made between the more traditional methods and indirect method of NaOH 5% extraction followed by colorimetric analyses. It was observed that the content of NaOH 5% extract correlates very well with pulp xylan content and reasonably well with the pentosan content. It is concluded that the 5% NaOH solubility method can be used in replacement of the other two, since it is faster, simpler and less costly to carry out than the others.